(untitled) (Fiep Bulletin - online, 2011)
This study aimed to show the benefits of walking to a better quality of life in the Third Age. Thus, the relevance of this article is related to the incentive to walk as daily physical activity as prevention abilities of the elderly, since the physical changes are largely from immobility. The lack of movement often leads to weakness and muscle shortening, resulting in difficulty of moving and intermittently affecting physiological functions of the elderly. The objective of this paper is to present the point of view of the physical education teacher, the relationship between walking and physical activity related to the elderly for a better quality of life, and specifically show the effects of regular physical activity, such as walking for the elderly and their benefits; encourage the elderly to physical activity, understand the profile of older practitioners and non practitioners of physical activities; quantify some effects of walking and physical activity for people aged over 60 years and, offering better quality of life by walking for people with advanced age. Methodologically, this article is characterized by an exploratory, qualitative descriptive, which contains a review and literature searches, articles and journals, aimed at providing theoretical support for this study. Thus, one can observe that the regular practice, especially walking, are good only for the elderly, resulting in improved living conditions and health, maintaining the harmony of mind and body.